Pharmaceutical Assessment of Watermelon Rind Pectin as a Suspending Agent in Oral Liquid Dosage Forms. (7th November 2022) - Owusu, Frederick William Akuffo; El Boakye-Gyasi, Mariam; Bayor, Marcel Tunkumgnen; Osei-Asare, Christina; Johnson, Raphael; Osei, Yaa Asantewaa; Asare, Victoria Agyeibea; Mensah, Kezia Akoley; Acquah, Prince George; Otu, Desmond Asamoah Bruce; Asante, Rocklyn
Abstract : Pectin is a high molecular weight polymer which is present in virtually all plants where it contributes to the cell structure. Pectin is a high valuable food ingredient widely used as a gelling agent and thickening agent with limited use in the pharmaceutical industry. The objective of this study is to evaluate the suspending properties of pectin from watermelon rind. Tragacanth was used as a standard suspending agent to which the suspending properties of pectin from watermelon rinds were compared with. The extracted pectin was subjected to phytochemical and physiochemical characterization for its safety and suitability to use as a suspending agent. Paracetamol suspensions were formulated using tragacanth concentrations of 0.5% w/v, 1% w/v, and 2% w/v and compared with paracetamol suspensions containing the same concentrations of watermelon pectin. The suspensions were all tested for their pH, sedimentation rate, sedimentation volume, flow rate, and ease of redispersibility over a period of 4 weeks. At the end of the 4-week period, all formulated suspensions had no changes in their pH values. Suspensions containing the extracted pectin had a lower rate of sedimentation and ease of redispersibility compared to that of tragacanth. In addition, their sedimentation volumes as well as flow rates were comparable to that of the tragacanth formulations. Ultimately, pectin from watermelon rind can serve as a suitable alternative to tragacanth in formulation of pharmaceutical suspensions.